Pengaruh Aplikasi Scratch terhadap Minat Belajar Matematika Siswa Kelas 7 SMPIT Islmaic City Menggunakan Metode UTAUT - Zahra, Zahra; Aprillia, Aprillia; Fara Mutia; Lilik Yuliawati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Mathematics is a basic science that humans always use to help solve all life problems, because to solve problems that require computation such as calculating finances, calculating time differences, most people think that learning mathematics seems difficult, complicated, and boring so mathematics lessons are included in the category of lessons that are less popular with many students. This study aims to analyze the effect of the Scratch application on interest in learning mathematics using the Unified Theory of Acceptance and Use of Technology (UTAUT) at SMPIT Islamic City. This study examines performance expectations (Performance Expectancy), effort expectations (Effort Expectancy), and facilitating conditions (Facilitating Conditions) on Scratch on students' Interest in Learning Mathematics. The research sample consisted of 51 7th-grade students of SMPIT Islamic City. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that performance expectations (Performance Expectancy) had a positive and significant effect on Interest in Learning Mathematics (t count = 3.827, p <0.05). Furthermore, effort expectancy does not have a positive and significant influence on Mathematics Learning Interest (t count = 1.140, p > 0.05). Finally, the condition of the facilities has a positive and considerable influence on Mathematics Learning Interest (t count = 2.841, p < 0.05). Simultaneously, the three independent variables significantly influence Mathematics Learning Interest, with an F count value of 26.386 and an R square of 0.627.